2016
DOI: 10.3892/etm.2016.3838
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-497 is associated with upregulation of synuclein γ in patients with osteosarcoma

Abstract: Abstract. The present study aimed to investigate the effects of microRNA (miRNA/miR)-497 expression levels on the expression levels of synuclein γ (SNCG) in serum samples, as well as osteosarcoma and lung-metastatic tissue samples, from patients with osteosarcoma. Between December 2010 and August 2013, fasting peripheral blood was collected from 36 patients with osteosarcoma for serum separation. In addition, osteosarcoma and lung metastatic tissues were resected from 15 osteosarcoma patients with lung metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…In our cohort, we revealed that the higher level of SNCG had a significant correlation with worse PFS and OS in HGSOC patients, which indicated its role in HGSOC as well as a novel prognostic marker of HGSOC aggression. Some studies have shown that SNCG could be detected in the circulation of patients with cancer [29,30]. Future studies are needed to evaluate the potential of serum SNCG levels as a biomarker for HGSOC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, we revealed that the higher level of SNCG had a significant correlation with worse PFS and OS in HGSOC patients, which indicated its role in HGSOC as well as a novel prognostic marker of HGSOC aggression. Some studies have shown that SNCG could be detected in the circulation of patients with cancer [29,30]. Future studies are needed to evaluate the potential of serum SNCG levels as a biomarker for HGSOC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating miRNAs not only facilitate early cancer diagnosis, but also aid in monitoring tumor metastasis. Reports have found substantial downregulation of miR-497-5p expression in primary osteosarcoma tissues, metastases, and serum versus healthy controls [33,34]. The results from the CNUH cohort indicate that elevated miR-92b-3p expression was associated with increased tumor volume and lymph node metastasis in OSCC.…”
Section: Discussionmentioning
confidence: 80%
“…Τέλος, το SNCG mRNA (πιθανά με ρόλο στην ενεργοποίηση του MAPK and Elk-1 μονοπατίου) και τα επίπεδα έκφρασης πρωτεΐνης του ήταν σημαντικά αυξημένα σε ιστούς οστεοσαρκώματος (Ρ <0,01), στο αίμα των ασθενών με οστεοσάρκωμα (Ρ <0.01) και σε ιστούς μεταστατικούς στον πνεύμονα (Ρ <0,01). Το miR-497 ήταν σημαντικά μειωμένο και στα τρία δείγματα.Ως εκ τούτου, μειωμένη ρύθμιση του miR-497 μπορεί να οδηγήσει στην ανάπτυξη και μετάσταση του οστεοσαρκώματος μέσω της αυξημένης ρύθμισης SNCG mRNA (γονίδιο-στόχος) [310].…”
Section: στεπίδραση σε μοριακούς παράγοντες και οδούς σήματοςunclassified